Pengaruh permainan blok bongkar pasang terhadap kemampuan mental rotation pada dewasa awal - Rio Saputra; Udi Rosida Hijrianti; Miqdad Daly Ahmad (Cognicia, 2026)
Previous studies have shown that playing with Lego is significantly associated with mental rotation ability in children. This study aimed to examine the effect of block construction play on mental rotation ability in young adults. The study employed a quantitative experimental approach using a non-randomized pre-test post-test control group design. The participants were 30 young adults, divided into 15 individuals in the experimental group and 15 in the control group, all with low to moderate mental rotation ability. Participants were selected using purposive sampling. Mental rotation ability was measured using a mental rotation task. Data were analyzed using the Mann-WhitneyU test to compare scores between groups and the Wilcoxon signed-rank test to compare pre-test and post-test scores within each group. The results showed a significant difference between the experimental and control groups at post-test (p = 0.009 < 0.05). In addition,the experimental group showed a significant improvement (p = 0.002 < 0.05), while the control group showed no significant change (p = 0.189 > 0.05). These findings indicate that block construction play has a positive effect on improving mental rotation ability in young adults with characteristics similar to those of the study participants.